Application of metagenomic next-generation sequencing in the diagnosis of urinary tract infection in patients undergoing cutaneous ureterostomy - Huang, Rong; Yuan, Qian; Gao, Jianpeng; Liu, Yang; Jin, Xiaomeng; Tang, Liping; Cao, Ying (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: Urinary tract infection (UTI) is an inflammatory response of the urothelium to bacterial invasion and is a common complication in patients with cutaneous ureterostomy (CU). For such patients, accurate and efficient identification of pathogens remains a challenge. The aim of this study included exploring utility of metagenomic next-generation sequencing (mNGS) in assisting microbiological diagnosis of UTI among patients undergoing CU, identifying promising cytokine or microorganism biomarkers, revealing microbiome diversity change and compare virulence factors (VFs) and antibiotic resistance genes (ARGs) after infection. Methods: We performed a retrospective cohort study of 50 consecutive CU patients from December 2020 to January 2021. According to the clinical diagnostic criteria, samples were divided into infected group and uninfected group and difference of urine culture, cytokines, VFs, microorganism and ARGs were compared between the two groups. Results: Inflammatory responses were more serious in infected group, as evidenced by a significant increase in IFN-α (p=0.031), IL-1β (0.023) and IL-6 (p=0.018). Infected group showed enrichment in certain pathogenic organisms, including Serratia symbiotica, Citrobacter braakii, Pseudomonas aeruginosa, Citrobacter youngae, Proteus penneri, and Klebsiella pneumoniae. According to clinical diagnose, mNGS showed higher level of sensitivity with an 86% clinical acceptance rate. A significant reduction in the Shannon and Simpson indices indicated a lower diversity in the urinary microbiome due to infection. Virulence factors were enriched in infected group, particularly in P. aeruginosa and Enterococcus faecalis. Finally,42 ARGs that were closely related with a resistant Antimicrobial susceptibility testing (AST) phenotype were identified covering 14 antibiotics and eight drug classes.